2018
DOI: 10.1186/s12887-018-1317-2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical respiratory score predicts paediatric critical care disposition in children with respiratory distress presenting to the emergency department

Abstract: BackgroundRespiratory distress is a common presenting complaint in children brought to the Emergency Department (ED). The Clinical Respiratory Score (CRS) has shown promise as a screen for severe illness in High Income Countries. We aimed to validate the admission CRS in children presenting to the ED of a Low-to Middle Income Country.MethodsChildren (1 month to 16 years) presenting with respiratory distress to the ED of the Aga Khan University Hospital, Karachi, Pakistan, between November 2015 to March 2016, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
1
22
0
3
Order By: Relevance
“…Patients with a positive COVID-19 RT-PCR (reverse transcription-polymerase chain reaction) test but without clinical and radiological signs of the disease were considered asymptomatic; patients with symptoms of an upper respiratory tract infection such as fever, fatigue, myalgia, cough, sore throat and runny nose but a normal respiratory system examination were considered to have a mild disease; and patients with signs of pneumonia and the complaints of fever and cough but without symptoms of dyspnoea and hypoxemia were considered to have pneumonia. Respiratory distress was defined as having tachypnoea and the need for supplementary oxygen [ 14 ]. Asymptomatic patients were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with a positive COVID-19 RT-PCR (reverse transcription-polymerase chain reaction) test but without clinical and radiological signs of the disease were considered asymptomatic; patients with symptoms of an upper respiratory tract infection such as fever, fatigue, myalgia, cough, sore throat and runny nose but a normal respiratory system examination were considered to have a mild disease; and patients with signs of pneumonia and the complaints of fever and cough but without symptoms of dyspnoea and hypoxemia were considered to have pneumonia. Respiratory distress was defined as having tachypnoea and the need for supplementary oxygen [ 14 ]. Asymptomatic patients were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the current study goes in line with Alexandrino et al [13] found that the highest percent of children presented a moderate respiratory impairment of the respiratory health condition mainly due to the presence of rhinorrhea and secretions. Other study conducted by Nayani et al [24] stated that regarding Clinical Respiratory scores (CRS), about one third of children had mild respiratory condition, more than half in moderate and nine percent in sever category. Post the intervention, the total scores improved with obvious decrease in the percent of children having a moderate CRS.…”
Section: Discussionmentioning
confidence: 98%
“… 15 A study conducted in the ED of the Aga Khan University Hospital, Karachi investigated the outcomes of children aged between one month to 16 years using the Clinical Respiratory Score (CRS) and concluded that patients with higher scores were more likely to be admitted to the pediatric critical care unit. 16 As compared to the PRAM score, CRS takes into account the mental status and appearance of the child and does not require expert training to use.…”
Section: Discussionmentioning
confidence: 99%